2015
DOI: 10.1152/japplphysiol.00101.2015
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative capacity and glycogen content increase more in arm than leg muscle in sedentary women after intense training

Abstract: The hypothesis that the adaptive capacity is higher in human upper- than lower-body skeletal muscle was tested. Furthermore, the hypothesis that more pronounced adaptations in upper-body musculature can be achieved by "low-volume high-intensity" compared with "high-volume low-intensity" exercise training was evaluated. A group of sedentary premenopausal women aged 45 ± 6 yr (± SD) with expected high adaptive potential in both upper- and lower-extremity muscle groups participated. After random allocation to hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 35 publications
5
40
3
Order By: Relevance
“…In multiple sprint sports such as football the recovery from intense exercise is essential for performance (Mohr et al 2005), and the recovery capacity has been linked to the muscle oxidative capacity (Bangsbo 1994) and is upregulated after high-intensity training regimes (Burgomaster et al 2005;Nordsborg et al 2015). In the present study no relationship was found between neither CS or HAD activity nor cytochrome c oxidase IV protein expression and any of the high-intensity game variables.…”
Section: Figcontrasting
confidence: 57%
See 1 more Smart Citation
“…In multiple sprint sports such as football the recovery from intense exercise is essential for performance (Mohr et al 2005), and the recovery capacity has been linked to the muscle oxidative capacity (Bangsbo 1994) and is upregulated after high-intensity training regimes (Burgomaster et al 2005;Nordsborg et al 2015). In the present study no relationship was found between neither CS or HAD activity nor cytochrome c oxidase IV protein expression and any of the high-intensity game variables.…”
Section: Figcontrasting
confidence: 57%
“…Moreover, HAD and CS have recently been shown to display different adaptation patterns to exercise training (Nordsborg et al 2015).…”
Section: Figmentioning
confidence: 99%
“…Thus, additional highintensity intermittent training carried out during the competitive season markedly facilitates fatigue resistance during repeated intense actions, which is likely to be highly important in an intense intermittent sport such as volleyball [37,40]. In the present study no physiological measurements were obtained, but several studies during the last decade have shown very large effects on muscle oxidative capacity [8,12,33], muscle ion transports [29,39], type IIx muscle fibre area [16] and muscle oxygen uptake kinetics [19] after high intensity training, which all are suggested to affect repeated sprint performance.…”
Section: Discussionmentioning
confidence: 67%
“…Nevertheless, there are notable differences in upper and lower limb involvement between swimming and running. For instance, when high‐intensity swimming is directly compared to high‐intensity soccer, metabolic adaptations differ between arms and legs . Moreover, they are performed in different environmental media, so it is reasonable to suggest that these 2 exercise modes elicit different metabolic responses.…”
Section: Introductionmentioning
confidence: 99%